Edible insects as functional foods: bioactive compounds, health benefits, safety concerns, allergenicity, and regulatory considerations - Alejandro Ruiz, Fernando E.; Ortega Jácome, Julio F.; Tejera, Eduardo; Alvarez-Suarez, José M. (Frontiers in Nutrition, 2025)
The growing demand for sustainable and nutrient-rich food sources has positioned edible insects as a viable alternative to traditional animal-based proteins. This review explores the bioactive properties and food safety considerations of edible insects, emphasizing their potential health benefits and the challenges associated with their widespread consumption. Research has identified bioactive compounds in insects with antioxidant, antimicrobial, immunomodulatory, cardioprotective, and digestive health-promoting properties, highlighting their potential as functional foods for preventing or managing chronic diseases such as cardiovascular conditions and inflammatory disorders. Additionally, this review examines findings related to contaminants in edible insects, including heavy metals, microbial pathogens, and allergens, which could pose health risks. Certain insect species have shown accumulation of heavy metals, such as cadmium and lead, depending on their diet and environment. Moreover, microbial contamination, including bacteria, fungi, and parasites, can occur if farming and processing conditions are not properly controlled. Furthermore, insect proteins exhibit cross-reactivity with allergens found in crustaceans and dust mites, raising concerns for individuals with food allergies. For edible insects to be successfully integrated into global food systems, further technological advancements, regulatory oversight, and consumer acceptance strategies must be implemented. Addressing these challenges will enable edible insects to become a key component of sustainable food systems, contributing to global nutrition, environmental sustainability, and human health.